A translocation-competent pore is required for Shigella flexneri to escape from the double membrane vacuole during intercellular spread - Raab, Julie E.; Harju, Tucker B.; Toperzer, Jody D.; Duncan-Lowey, Jeffrey K.; Thomas, Connon I.; Darehshouri, Anza; Goldberg, Marcia B.; Russo, Brian C. (mBio, 2025)
The type 3 secretion system (T3SS) is required for virulence inmany bacterial pathogens that infect humans. The T3SS forms a pore through which virulence proteins are delivered into host cells, enabling bacterial infection. Our work investigates the Shigella translocon pore protein IpaC, which is essential not only for bacteria to invade cells but also for bacteria to spread between cells. The ability to spread between cells is essential for pathogenesis; thus, understanding the mechanisms that enable spread is important for determining how S. flexneri infection causes illness. We show that IpaC delivers virulence factors across the host membrane for S. flexneri to efficiently spread. This study furthers our understanding of the mechanisms involved in T3SS secretion and of translocon pore function during S. flexneri intercellular spread.